Franklin wants a pet - Bourgeois, Paulette; Clark, Brenda (New York : Scholastic, 1995)
Franklin the turtle wants a pet, and when his parents finally agree, they are surprised to see what he chooses.
3.0
K-3
K-3
390
Keywords: Turtles -- Fiction; Pets -- Fiction; Parent and child -- Fiction; Turtles -- Fiction; Pets -- Fiction; Parent-child relationship -- Fiction